Third‐Trimester Cardiovascular Function and Risk of Hypertensive Disorders of Pregnancy - Frederikke Lihme; Saima Basit; Lisa G. Persson; Maria O. Larsen; Karin H. Lauridsen; Jacob A. Lykke; Anita S. Andersen; Annette Thorsen‐Meyer; Kasper Pihl; Mads Melbye; Jan Wohlfahrt; Heather A. Boyd (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background Whether cardiovascular dysfunction is associated with preeclampsia in women without fetal growth restriction (FGR) is unclear. Our objective was to investigate associations between third‐trimester cardiac output (CO) and systemic vascular resistance and risk of hypertensive disorders of pregnancy in women with and without FGR. Methods and Results A case–cohort study in 906 pregnant women in Denmark with repeated third‐trimester cardiac function assessments was performed using the Ultrasound Cardiac Output Monitor 1A. Using Cox regression, we compared rates of hypertensive disorders of pregnancy in women with low, normal, and high CO and normal and high systemic vascular resistance, by FGR status and gestational age, and evaluated associations between a third‐trimester drop in CO or increase in systemic vascular resistance and preeclampsia risk in women without FGR. The analysis included 249 women with preeclampsia (42 with FGR) and 119 women with gestational hypertension. Low CO was strongly associated with preeclampsia at <37 weeks (women with FGR: hazard ratio [HR], 5.25 [95% CI, 1.26–21.9]; women without FGR: HR, 2.19 [95% CI, 1.07–4.48]). Our results also suggested an association between low CO and preeclampsia at ≥37 weeks among women without FGR (HR, 1.31 [95% CI, 0.84–2.03]), and between a third‐trimester drop in CO >75th percentile and preeclampsia in women without FGR (odds ratio, 1.91 [95% CI, 0.84–4.36]). High systemic vascular resistance was strongly associated with increased rates of all forms of hypertensive disorders of pregnancy. Conclusions Low CO is associated with preeclampsia risk in women with and without FGR, particularly before 37 weeks. Repeated measurements of third‐trimester cardiovascular function might identify women without FGR for monitoring for preeclampsia, but this result needs to be confirmed in other studies.